Pachakutik: Indigenous Movements and Electoral Politics in Ecuador - Becker, Marc (Rowman & Littlefield Publishers, 2010)
This authoritative book provides a deeply informed overview of one of the most dynamic social movements in Latin America. Focusing on contemporary Indigenous movements in Ecuador, leading scholar Marc Becker traces the growing influence of the Confederation of Indigenous Nationalities of Ecuador (CONAIE), which in 1990 led a powerful uprising that dramatically placed a struggle for Indigenous rights at the center of public consciousness. Activists began to refer to this uprising as a "pachakutik," a Kichwa word that means change, rebirth, and transformation, both in the sense of a return in time and the coming of a new era. Five years later, proponents launched a new political movement called Pachakutik to compete for elected office. In 2006, Ecuadorians elected Rafael Correa, who many saw as emblematic of the new Latin American left, to the presidency of the country. Even though CONAIE, Pachakutik, and Correa shared similar concerns for social justice, they soon came into conflict with each other. Becker examines the competing strategies and philosophies that emerge when social movements and political parties embrace comparable visions but follow different paths to realize their objectives. In exploring the multiple and conflictive strategies that Indigenous movements have followed over the past twenty years, he definitively documents the recent history and charts the trajectory of one of the Americas' most powerful and best organized social movements.